Tracing the History and Cultural Dynamics of Kuda Lumping in Ngantang District, Malang Regency - Putri, Daifanny Aurelya Sugiono; Zibran, Rizal; Muslimin, Moch.; Fauziyah, Nailul (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The cultural practice of Kuda Lumping in Ngantang District has persisted for centuries, yet scholarly attention at the sub-district level remains limited. Existing studies generally examine Kuda Lumping as a Javanese performing art, but rarely explore how ritual structures, symbolic elements, and local historical narratives interact within a single community context. Addressing this gap, the present study investigates the historical development and cultural dynamics of Kuda Lumping in Ngantang using an ethnographic approach grounded in ritual performance theory and cultural resilience frameworks. Data were collected through participant observation, in-depth interviews, and documentation involving 11 key cultural actors, including community leaders, handlers, dancers, musicians, and village elders. Spradley’s analytical model domain, taxonomy, componential, and cultural theme analysis was applied to interpret cultural meanings embedded in the tradition. The findings reveal that Kuda Lumping in Ngantang, introduced in the 17th century through local historical figures, has undergone adaptive transformations while retaining core ritual elements such as offerings, prayers, and trance states (ndadi). These practices illustrate how the community negotiates continuity and change through symbolic performance. The study contributes to Javanese performance-ethnography literature by conceptualizing cultural adaptation within Kuda Lumping as a form of ritual resilience that enables the tradition to remain socially relevant in contemporary settings.